Social Cohesion of Padang City Vocational School Students - Syarifah Wahidah; Firman Firman (International Journal of Applied Counseling and Social Sciences, 2020)
Brawls among students in various regions of Indonesia are still often the main topic in various media. Even though student brawls are not new in Indonesia, in recent years, the community has felt uneasy because brawls increasingly threaten a sense of security in the community. When explored further, a lack of student social cohesion causes student brawl. This study aims to provide an overview of the social cohesion of vocational students in Padang. This research is a descriptive study with a quantitative approach using a data collection instrument in the form of a social cohesion questionnaire with a validity greater than 0,404 and a reliability of 0,936. The subjects of this study were vocational high school students in Padang. The subjects were chosen by simple random sampling technique. This study applied data analysis with descriptive analysis. The results of this study indicate that the students' social cohesion consists of various dimensions. Each dimension has a different percentage. Dimension Inclusion has the lowest percentage that is 10%, dimension Participation as a percentage of 23%, dimension Recognition and Appreciation has a percentage of 25%, and dimension Sense of Belonging has the highest percentage, which is 42%.